Understanding environmental pollution - Hill, Marquita K. (Marquita Kaya) (Cambridge : Cambridge University Press, 2010)
This popular textbook has been updated to deliver an essential overview of global, corporate and individual environmental pollution issues.
CONTENTS: Understanding pollution -- Reducing pollution -- Chemical toxicity -- Chemical exposures and risk assessment -- Ambient air pollution -- Acid deposition -- Global warming -- Stratospheric ozone depletion -- Water pollution -- Drinking water -- Solid waste -- Hazardous waste -- Energy -- Persistent, bioaccumulative and toxic -- Metals - - Pesticides -- Pollution at home -- Zero waste, zero emissions -- Chemistry - basic concepts -- Index.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Pollutants; Pollution